Health protection for healthcare workers in COVID-19 times and responses to the pandemic - de Almeida, Ildeberto Muniz [UNESP] (FapUNIFESP (SciELO), 2020)
Objective: to discuss challenges for developing and implementing response and strategic readiness plans against COVID-19. Methods: based on the World Health Organization recommendations, which emphasizes three groups of objectives to be pursued, we advocate including the topic of health protection for health workers within the scope of its third objective: “Minimize the impact of the epidemic on health systems.” Discussion: the central argument adopted is that the emphasis on the use of PPE, social etiquette and hygiene measures can potentially minimize the importance of the engineering and administrative controls measures in preventing the disease. We highlight the need of training workers to recognize risk situations associated with the difficulties of the new activities that emerged during the pandemic, with emphasis on new interactions between healthcare professionals and also between other workers, as well as on new instruments and contexts related to the epidemic situation. The costs of the impacts on workers’ health tend to increase due to degradation of work conditions and the fast evolution of the disease. One of the response programs challenges is how to recognize and respond quickly to the changes that lead to new risks.
Proteção da saúde dos trabalhadores da saúde em tempos de COVID-19 e respostas à pandemia
Keywords: COVID-19; health workers; infectious diseases; occupational health